KAPASITAS PEMERINTAH NAGARI SILAYANG DALAM MENGELOLA POTENSI NAGARI SILAYANG UNTUK MENINGKATKAN PENDAPATAN ASLI NAGARI SILAYANG KECAMATAN MAPAT TUNGGUL SELATAN KABUPATEN PASAMAN PROVINSI SUMATERA BARAT TAHUN 2018 - Alfajri, Mustafa; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Nagari Silayang is one of the villages in Indonesia that has considerable natural and human resource potential. However, even though it has abundant potential, the village's original income (PADes) is still low. This can hinder the development and welfare of the village community as a whole. Therefore, it is necessary to manage village potential that is appropriate and sustainable to increase the village's original income and the welfare of the people of Silayang Village. This study aims to find out how the Capacity Development of the Nagari Silayan Government in Managing the Potential of Nagari Silayang to Increase Nagari Silayang's Original Income in 2018. This research uses a qualitative approach with data collection techniques through interviews and documentation. The results of this study show that the management of the potential of Nagari Silayang by the Nagari Silayang government has been carried out by strengthening human resources, strengthening organizations and institutional reforms to encourage the Nagari Silayang government to increase the village's original income through effective management of Nagari potential. The obstacles that occur in managing the potential of the Nagari Silayang area are human resources, capital and the environment. The capacity development of the Nagari Silayang government in managing its regional potential has not been carried out properly, this is due to obstacles in developing the capacity of the Nagari government such as weak human resources and limited village supervision. Keywords : The Capacity Of The Nagari Silayang Government, Potential Management